Curriculum Evaluation: CIPP Model of the Youth Scientific Group (KIR) extracurricular - Diah Ambarumi Munawaroh; Enik Kurniawati (JEET, Journal of English Education and Technology, 2022)
The focus of curriculum evaluation can be on the curriculum's outcomes (outcomes-based evaluation) and the components of the curriculum (intrinsic evaluation). The outcomes-based evaluation focuses on curriculum evaluation that is most often carried out. The purpose of this evaluation is that the evaluator can provide suggestions or input so that future extracurricular activities at MTsN 2 Kota Kediri can run better. This evaluation uses the CIPP evaluation model (Context, Input, Processes, and Product) in extracurricular activities in the KIR field at MTsN 2 Kota Kediri. Based on the evaluation results obtained data from (1) the context aspect, overall, very good with a total average of 91.67%. (2) The input aspect obtained an average of 90.60%. (3) The process aspect is outstanding, with a total average of 89.92%. (4) The product aspect is excellent, with an average of 91.65%. From the evaluation results, it can be stated that further improvements include the need for the establishment of a KIR organization, improving facilities and supporting facilities